Insulinotropic Properties of Several Malaysian Herbs and Ganoderma Species - Bastami, Mohd Saufi (2006)
Diabetes Mellitus incident is currently one of the major and common diseases in Malaysia and increasing every year. To date, no herbs or drugs are able to completely cure the disease. In this study, insulinotropic properties of Malaysian herbs were investigated using pancreatic P cells BRIN-BD1 1 . Three out of 13 herbs samples studied were belongs to fungi (Ganoderma sp). The studied showed seven samples are able to induce insulin secretion over 200 % by BRIN-BD11 cell lines. Based on traditional practitioner reports, Gynuraprocumbens was choosed for further investigation on its antihyperglycemic properties. Glucose tolerance test were carried on normal and streptozotocin-induced diabetic rats showed at 1000 mglkgl b.w Gynura procumbens methanolic extract was able to reduce blood glucose level in rats. Toxicity towards BRIN-BD11 cells was analyzed using MTT assay and alkaline comet assay. Toxicity levels at ICS0 was 300 uglml using MTT assay. Furthermore, Alkaline Comet Assay has proved this toxicity is not due to DNA damage in BRIN-BDl 1 cells. Acute toxicity was carried on ICR strain mice for 14 days. Gynuraprocumbens did not show any toxicity at concentration 7 glkg b.w after administered orally. These results suggest Gynura procumbens and other herbs contain active constituents and have potentials for diabetes treatment.